1987
DOI: 10.1002/art.1780300512
|View full text |Cite
|
Sign up to set email alerts
|

Plasma hydroxychloroquine concentrations and efficacy in rheumatoid arthritis

Abstract: Plasma levels of hydroxychloroquine (HCQ) and its metabolites were measured, by high performance liquid chromatography, in 37 rheumatoid arthritis patients who could be clearly distinguished As responders (n = 28) or nonresponders (n = 9) to HCQ, 400 mglday. Efficacy in both groups was determined by the patients' erythrocyte sedimentation rates, joint counts, morning stiffness, globai assessments, Concurrent drug therapies, and grip strength. The response rate was 76%. Responders had a mean HCQ level of 213 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…This fact may provide an explanation for the different conclusions of the study reporting a positive relationship between blood hydroxy chloroquine concentrations and clinical outcomes (Tett et al 1993) and the studies reporting no relationship between plasma or serum hydroxychloroquine concentrations and effect (Laaksonen et al 1975;Miller et al 1987). In the former, cross-sectional study, patients with clinical measures indicating less active rheumatoid arthritis had statistically significantly higher blood concentrations of hydroxychloroquine than those with more active disease (Tett et al 1993).…”
Section: Concentration-effect Relationshipsmentioning
confidence: 92%
“…This fact may provide an explanation for the different conclusions of the study reporting a positive relationship between blood hydroxy chloroquine concentrations and clinical outcomes (Tett et al 1993) and the studies reporting no relationship between plasma or serum hydroxychloroquine concentrations and effect (Laaksonen et al 1975;Miller et al 1987). In the former, cross-sectional study, patients with clinical measures indicating less active rheumatoid arthritis had statistically significantly higher blood concentrations of hydroxychloroquine than those with more active disease (Tett et al 1993).…”
Section: Concentration-effect Relationshipsmentioning
confidence: 92%
“…They are not comparable; plasma concentrations are the lowest, and whole blood concentrations are the greatest. Serum concentrations exceed plasma concentrations because platelets concentrate 4AQs, and upon coagulation of the blood the platelet contents are released into the serum [ 139 ]. Plasma levels of chloroquine effective against malaria are 10 [ 16 , 37 , 78 , 89 ].…”
Section: Clinical Uses and Dosingmentioning
confidence: 99%
“…Although Frisk-Holmberg et al (1979) suggested that chloroquine has a narrow therapeutic serum concentration range, no minimally effective concentration for 'antirheumatoid' activity for either agent has been accurately delineated (Maksymowych & Russell 1987). Miller et al (1987) found no relationship between plasma concentrations and the efficacy of hydroxy-chloroquine 400 mg/day. Their inference, however, is not conclusive: they used only 1 dose, rather than a wide dosage range, and also took blood samples at unspecified times.…”
Section: Antimalarial Drugsmentioning
confidence: 76%
“…There have never been any controlled trials involving chloroquine, and a randomised controlled clinical trial with hydroxy-chloroquine 3 to 6 mg/kg showed no statistical advantage over placebo ). However, Miller et al (1987) were able to divide their 37 adult rheumatoid arthritis patients into 28 responders and 9 nonresponders to hydroxy-chloroquine.…”
Section: Antimalarial Drugsmentioning
confidence: 95%